G516(P) Effect of cygnet training programme at improving parents' knowledge and confidence in managing autistic children at an integrated neurodevelopmental service in south eastern england. (May 2019) - Ayyash, HF; Ogundele, MO; Cuff, L; Azmi, L; Weisblatt, E
Abstract : Background: Autism Spectrum Disorders (ASD) are neurodevelopmental social communication disorders, with common problems for families including sleep, anxiety, difficulty with change, sensory processing difficulties and disruptive behaviour. The CYGNET programme was developed in 2003 by the UK-based charity Barnado as an information group for parents of children diagnosed with ASD. It is the primary post-diagnostic intervention offered in the Autism pathway in the Peterborough Neurodevelopmental Service. Parents are routinely invited to attend the 6 session programme which aims to increase their understanding of ASD. Aim: To evaluate the effectiveness of the CYGNET course in increasing parents' confidence in dealing with common situations relating to their child's ASD. Method: Using an observational study design, data were collected retrospectively, using questionnaires completed by parents attending courses over a 12 month period. 68 parents rated their confidence in dealing with 15 different common situations on a 6-point scale (0=no confidence to 5=completely confident), at the start and end of the course. Paired t-test was used to compare total and item scores before and after the course. 15 questionnaires were excluded because of incomplete data leaving 53 participants. Results: Self-rated parents'/carers' confidence in dealing with the 15 situations was significantly greater following the programme completion in 51 (96%) of the respondents (Figure 1). The mean increase in total score was 18.75 (95% CI 16.11–21.40), t=−14.23, p<0.0001. The confidence rating of all the participants increased by over one point on average for each of the 15 situations (mean 4.0 vs 2.8, mean difference 1.26±0.16, 95% CI 1.16–1.35, t=29.94, df 14, p<0.0001). Conclusion: This study suggests that the CYGNET programme is effective in increasing the confidence of parents in dealing with difficulties arising from supporting young people with ASD. It would be useful to also evaluate longer-term effects of the CYGNET programme on the parents following attendance.